RISK COMMITTEE CHARACTERISTICS AND BANK RISK-TAKING - Yudhi Kuncoro Aji; Helti Nur Aisyiah (International Conference on Economics, Management, Business, and Accounting, 2024)
This study aims to empirically prove the characteristics of risk committees on bank risk taking. The research hypothesis is based on agency theory and resource dependence theory. The sampling technique of this study used a purposive sampling method with a total data of 11 banks during the period 2017-2022 and a total of 66 observations. The results of this study indicate that the variables of risk committee size, risk committee independence, and risk committee with expertise in economics have a negative effect on bank risk taking, while the variables of risk committee meetings and risk committees from abroad have a positive effect on bank risk-taking. However, the variables of gender diversity in risk committees and risk committees with doctoral degrees do not affect bank risk taking.